THE PLACE OF PHILOSOPHICAL-PSYCHOLOGICAL INTERPRETATION IN LITERATURE - Abdullayeva Dilorom Nosir qizi; Qahramonov Q. Y. (Bright Mind Publishing, 2025)
This article discusses one of the current issues in literary criticism today - the concept of philosophical-psychological interpretation and the task of this issue. The role and importance of artistic psychologism in literature is revealed through the story “The Green Lantern” by Alexander Green, a prominent representative of world literature.
Keywords: Psychologism, human psyche, artistic image, artistic thought, social difference.